4G LTE Network Performance for XL Axiata provider in Lolong Belanti Area - Abdi Abdullah; Dikky Chandra; Zurnawita Zurnawita; Dinda Kurnia Illahi (International Journal of Wireless And Multimedia Communications, 2025)
This measurement aims to analyze the quality of the 4G LTE network and its relationship with the quality of service (QoS) parameters on the performance of TCP/IP provider XL Axiata in Lolong Belanti Village. The measurement results show that the network with the quality category "Good" to "Excellent" has a percentage value of RSRP 97.5%, SINR 75.52%, and Throughput is categorized as good (Good) based on KPI. In comparison, the network with the category "Poor" to "Fair" shows a percentage value of RSRP 2.5% and SINR 24.48%. The measurement also found that RSRP and SINR parameters significantly affect QoS, with increasing RSRP and SINR values associated with increasing Download Bandwidth, Upload Bandwidth, and Throughput. The highest quality was achieved in the "Excellent" SINR category, with a Download Bandwidth of 42.60 Mbps, an Upload Bandwidth of 28.30 Mbps, and a Throughput of 2,543 kbps. However, there was a significant decrease in the "Poor" category, especially in Download Bandwidth and Throughput. Factors such as packet loss, jitter, and delay were also analyzed, with the results showing that the highest packet loss occurred in the "Poor" category. In contrast, jitter and delay dominated the "Poor and Fair" categories. These findings indicate the importance of RSRP and SINR parameters in determining the quality of 4G LTE networks and their impact on user experience.